Research on inverse solution of shotcrete manipulators based on an improved bee colony algorithm - CHEN Hetian; CHENG Wenming; DU Run; ZHANG Zhipeng (Jixie chuandong)
ObjectiveThe shotcrete manipulator is an eight-degree-of-freedom redundant manipulator with prismatic joints, and its inverse kinematics is difficult to solve. Therefore, an improved bee colony algorithm was designed.MethodsFirstly, the D-H method was used to establish the kinematics model of the manipulator, and multi-constrained objective functions were constructed with the terminal pose error and best flexibility as optimization objectives. Then, chaotic mapping was introduced to initialize the honey source, and Levy flight was introduced to change the search strategy of the employed bees. The step length of the onlookers was adjusted adaptively, and the population diversity and the algorithm convergence speed were improved. Finally, the Matlab programming was used for simulation verification.ResultsThe results show that the convergence speed and the accuracy of the proposed algorithm are better than the traditional bee colony algorithms, the chaotic bee colony algorithm and the particle swarm algorithm, which proves the feasibility of the proposed algorithm, and has provided a new way to solve the inverse kinematics of the wet spray manipulator.